2022
DOI: 10.1111/hae.14620
|View full text |Cite
|
Sign up to set email alerts
|

Occupational integration of adults with severe haemophilia (INTHEMO): A study based on the FranceCoag registry

Abstract: Introduction Health of people with severe haemophilia (PwSH) improves thanks to the advancements in haemophilia care, giving them more opportunities in occupational integration. However, there is little literature on the occupational integration of PwSH. Objectives The main objective of our study was to assess the occupational integration of PwSH and to compare it with that of the general population. The secondary objective was to study the association between individual characteristics (sociodemographic, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(114 reference statements)
1
2
0
1
Order By: Relevance
“…An important reason for these differences is to be found in the impact of HIV and Hep C on the haemophilia population from 1980 onwards. A recent French study of the occupational integration of adults with severe haemophilia found that PWH had better education but lower employment, 14 similar to the trends in our analyses. Our results concerning increased prevalence of hypertension has been reported in several earlier studies of hypertension among PWH 15–17 .…”
Section: Discussionsupporting
confidence: 90%
“…An important reason for these differences is to be found in the impact of HIV and Hep C on the haemophilia population from 1980 onwards. A recent French study of the occupational integration of adults with severe haemophilia found that PWH had better education but lower employment, 14 similar to the trends in our analyses. Our results concerning increased prevalence of hypertension has been reported in several earlier studies of hypertension among PWH 15–17 .…”
Section: Discussionsupporting
confidence: 90%
“…11 • Participation in life: due to the burdens of therapy, physical limitations, and psychosocial consequences of the disease, the educational opportunities, free choice of occupation as well as sports and social activities are subject to limitations in patients with hemophilia. 12,13 Gene therapy has the potential to effect substantial improvements in PROs in the above-mentioned areas. Thus, consistently higher levels of the clotting factor could prevent the risk of severe bleedings and the development or progression of joint damage.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in life: due to the burdens of therapy, physical limitations, and psychosocial consequences of the disease, the educational opportunities, free choice of occupation as well as sports and social activities are subject to limitations in patients with hemophilia. 12 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation